2010
DOI: 10.1073/pnas.0913476107
|View full text |Cite
|
Sign up to set email alerts
|

Combination antibody treatment down-regulates epidermal growth factor receptor by inhibiting endosomal recycling

Abstract: Due to its common dysregulation in epithelial-based cancers and extensive characterization of its role in tumor growth, epidermal growth factor receptor (EGFR) is a highly validated target for anticancer therapies. There has been particular interest in the development of monoclonal antibodies (mAbs) targeting EGFR, resulting in two approved mAb-based drugs and several others in clinical trials. It has recently been reported that treatment with combinations of noncompetitive mAbs can induce receptor clustering,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
115
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(124 citation statements)
references
References 45 publications
9
115
0
Order By: Relevance
“…4D). This is in agreement with the notion that combining two different mAbs increases the inhibitory outcome (31).…”
Section: Discussionsupporting
confidence: 92%
“…4D). This is in agreement with the notion that combining two different mAbs increases the inhibitory outcome (31).…”
Section: Discussionsupporting
confidence: 92%
“…The antitumor actions of homocombinations of mAbs to EGFR and HER2 have been associated with forced internalization and subsequent receptor degradation in lysosomes (14,17,21). Furthermore, this mechanism might entail collapse of large antigen-antibody lattices into endocytic vesicles, which use clathrinas well as caveolin-mediated trafficking and avoid a recycling pathway that governs trafficking of EGFR bound to a single mAb (18,23). Interestingly, the data we present in Fig.…”
Section: Discussionsupporting
confidence: 47%
“…However, another way to improve the efficacy of mAbs to surface receptors comprises combinations of two or more mAbs, each targeting a distinct receptor's epitope. For example, it has been reported that certain pairs of anti-EGFR antibodies can accelerate receptor endocytosis and degradation (17), probably through a mechanism involving inhibition of receptor recycling (18). Consistent with these observations, a mixture of two anti-EGFR mAbs, called Sym004, inhibited cancer cell growth (14).…”
supporting
confidence: 61%
See 1 more Smart Citation
“…Our results build on and contribute to the emerging field of oligoclonal inhibitors of ErbB and other cell-surface receptors (51)(52)(53), which notably includes the approved combination of trastuzumab (Herceptin) and pertuzumab (Perjeta) targeting ErbB2 in metastatic breast cancer (57) and the early-stage clinical development of Sym004 targeting EGFR (5, 6). Our observations of near-complete downregulation of EGFR and enhanced CDC activity by MM-151 are consistent with these studies and provide an exciting prospect to elicit additional EGFR inhibition and pathway-extrinsic cytotoxicity beyond that achievable by single monoclonal antibodies.…”
Section: Discussionmentioning
confidence: 99%